Finite Element Analysis of the Structural Strength of Locomotive Cast Aluminum Gearbox Casing based on ANSYS - Zhao Junhua; Li Min (Jixie chuandong)
The 3D model of gearbox casing is built in design stage,and the FEA（ Finite Element Analysis） is carried out based on the ANSYS Software,the eight kinds of working conditions of locomotive runs normally are especially analyzed. Comparing with the Goodman curve,the stress of every point of gearbox model is within the Goodman curve. It is indicates that the gearbox casing meets the structural strength requirement,the rationality of structure design for the gearbox is confirmed.